A study of China's major domestic airlines' service quality at Shanghai's Hongqiao and Pudong International Airports. Issue 4 (2nd October 2017) - Jiang, Hongwei; Baxter, Glenn S.; Wild, Graham
Abstract: In a highly competitive market, service quality can be the core competitive advantage for airline's profitability and sustained development. This paper has investigated the differences in the passengers' expectations and perceptions of the service quality of China's four major domestic airlines: Air China, China Southern Airlines, China Eastern Airlines, and Hainan Airlines in China's domestic market. The results will assist airline management to improve service quality by reducing the difference. Surveys were conducted with domestic passengers at Shanghai Hongqiao Airport and Shanghai Pudong Airport in China. The results show that there are significant differences of service quality between passengers' expectations and perceptions among major Chinese airlines. Passengers consistently rate 'good safety records' as the first priority of seven SERVQUAL dimensions, but low price remains the most important factor that passengers consider when choosing a Chinese airline. The conclusions reached in this work suggest that Chinese airlines should consider improving service quality rather than providing cheaper air tickets in order to gain competitive advantage.